AIsolation and Characterization of a Heavy Metalreducing Enterobacteriaceae Bacterium Strain DRY 7 with the Ability to Assimilate Phenol and Diesel - Hamdan M.H.; Othaman M.A.; Suhaili Z.; Shukor M.S.; Halmi M.I.E.; Abdullah S.R.S.; Shamaan N.A.; Shukor M.Y. (Indian Society for Education and Environment, 2024)
Indexed by Scopus